Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Kantor Dinas Penanaman Modal dan Pelayanan Satu Pintu Provinsi Sumatera Barat - Malik, Agung Surya (Lembaga Yasin AlSys, 2025)
Organizational culture and work environment are two variables that are theoretically believed to influence employee performance, although previous research has shown inconsistent findings. This study aims to analyze the effect of organizational culture and work environment on employee performance at the Office of Investment and One-Stop Integrated Services (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu) of West Sumatra Province. A quantitative approach was used with a total sampling technique, involving 45 employees as respondents. The main instrument was a questionnaire that had been tested for validity and reliability, supported by an observation sheet. Data were analyzed using a t-test with the assistance of the latest version of SPSS software. The results show that organizational culture has a positive and significant effect on employee performance (p = 0.001 < 0.05), while the work environment does not show a significant effect (p = 0.209 > 0.05). These findings affirm that strengthening organizational culture through the instillation of collective work values, open communication, and shared commitment contributes more significantly to performance improvement than physical aspects of the work environment. The implications of this study highlight the importance of managerial strategies focused on building a healthy organizational culture as a means to enhance employee productivity.